Recent Advances on the Selection Methods of DNA‐Encoded Libraries - Huang, Yiran; Li, Xiaoyu (Chembiochem : a European journal of chemical biology, 2021)
DNA‐encoded libraries (DEL) have come of age and become a major technology platform for ligand discovery in both academia and the pharmaceutical industry. Technological maturation in the past two decades and the recent explosive developments of DEL‐compatible chemistries have greatly improved the chemical diversity of DELs and fueled its applications in drug discovery. A relatively less‐covered aspect of DELs is the selection method. Typically, DEL selection is considered as a binding assay and the selection is conducted with purified protein targets immobilized on a matrix, and the binders are separated from the non‐binding background via physical washes. However, the recent innovations in DEL selection methods have not only expanded the target scope of DELs, but also revealed the potential of the DEL technology as a powerful tool in exploring fundamental biology. In this Review, we first cover the “classic” DEL selection methods with purified proteins on solid phase, and then we discuss the strategies to realize DEL selections in solution phase. Finally, we focus on the emerging approaches for DELs to interrogate complex biological targets. DNA‐encoded chemical libraries (DEL) have become a major technology platform in drug discovery. Besides encoding method, DEL‐compatible chemistry, and analysis of large datasets, another important but less‐covered technological component of DELs is selection method. Although presently DEL selection is predominantly conducted with immobilized proteins on a matrix, the recent development of novel DEL selection methods has expanded the target scope and led to novel utilities of DELs. In this Review, we provide a comprehensive overview of DEL selection methods with a particular focus on the emerging approaches for DELs to interrogate complex biological targets.